GREENING THE DESERT AREAS OF NORTHERN NIGERIA: A PRACTICAL APPROACH TO FOOD SECURITY. - Abbas, Asiru Monday; Amanabo, Unekwu Hadiza (Innovare Journal of Sciences, 2017)
The study examined desertification, its causes and effects in the northern region of Nigeria and how a green initiative can be adopted to tackle the menace. The study opined that desertification can do severe damage to Nigerian agricultural production the bulk of which is concentrated in the northern region of the country if the problem is not properly handled. The study is of the opinion that greening the desert is a good approach that will help in reclaiming land areas lost to desertification and also help in transforming or regenerating the degraded land areas. Greening the desert has a lot of advantages that are of immense benefits to the environment, man and animals and some of these advantages include carbon sequestration, attraction of tourists, employment creation for the locals, natural rainfall generation, possible return of animal species that left as a result of desertification. The study suggested that halophytes, deep-rooted crops and trees that are of economic value should be planted. It is also recommended that programmes and policies designed to address the problem must move from paper policy to concrete action on the ground. There should be systematic and regular collection of data on the extent of desertification, damage and losses caused by desertification so that appropriate counter measures can be taken. Regular public enlightenment on sustainable use of natural resources was advocated as a de-desertification technique of immense proportion. Also, the Great Green Wall initiative designed to limit desertification should not be abandoned, it must be financially supported to achieve its objective. Keywords: Causes, Effects, Agriculture, Desert, Areas, Greening